A Critical Stylistic Analysis of Equivocation in a Religious Text - Mingher Obied Alshemmery, Iman; Mahdi, Salih (International Journal of Psychosocial Rehabilitation, 2020)
This study looks over equivocation in religious texts as one of the strategies employed by preachers in their sermons. Its intent is to exhibit the types, functions, and stylistic tools of equivocation utilized by a religious man who is regarded as an authorized person in his society. In a sense, that preacher cannot get rid of equivocation, and he appoints it using different stylistic tools. Additionally, he employs it for different reasons.